A Generalization of Von Neumann Regular Rings - Adil Jabbar (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper, we introduce a new ring which is a generalization of Von Neumann  regular rings and we call it a centrally regular ring. Several properties of this ring are proved and we have extended many properties of regular rings to centrally regular rings. Also we have determined some conditions under which regular and centrally regular rings are equivalent.